Condition of the Seagrass Ecosystem in the Waters of Jago-Jago Village, Central Tapanuli Regency, North Sumatra - Erika Endra Yanti; Joko Samiaji; Zulkifli Zulkifli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
This research was conducted in February-March 2023 in the coastal waters of Jago-Jago Village, Central Tapanuli Regency, North Sumatra Province. The purpose of this research was to determine the state of the seagrass ecosystem, including the type, density, coverage, and frequency of seagrass. This research used a purposive sampling method in determine sampling stations. At each station, 3 transect lines were applied, each 30 m long, and the distance between transects was 50 m. The results showed that the seagrass species at the study site was Enhalus acoroides. The highest average seagrass density is found at Station III, i.e., 47.44 ind/m2, included in a scale of 2, indicating it is classified as seagrass with rare conditions. Station I, with a density of 23.78 ind/m2, and Station II, with a density of 28.67 ind/m2, are included on the scale as seagrass with very rare conditions. The highest average coverage is at Station III (61.11%), and the lowest is at Station I (30.56%). Station III is in good condition, Station I and Station II are in damaged condition. The frequency of seagrass type 1, represented only by E. acoroides, is found at all research stations.